Evaluation of the Effectiveness of the Iralvex Gel on the Recurrent Aphthous Stomatitis Management. (14th October 2014) - Khademi, Heidar; Iranmanesh, Pedram; Moeini, Ali; Tavangar, Atefeh
Abstract : Introduction. As there is no definitive treatment for the recurrent aphthous stomatitis (RAS), most of the available therapies aim at decreasing pain and discomfort. The aim of this study was to investigate the effectiveness of the Iralvex gel on the RAS management. Material and Methods. In this double-blind and placebo-controlled clinical trial study, twenty patients were treated with the Iralvex gel and the other twenty patients were treated with placebo. In every participant complete healing of lesions, pain duration, and intensity were evaluated. Data were analyzed by independent t -test and analysis of variance. Results. Pain was relieved after 6.10 ± 0.29 days in the Iralvex group in comparison to 8.00 ± 0.33 days in the placebo group ( P value ≤0.001). Complete remission in the Iralvex group was after 6.80 ± 0.27 days and 10.20 ± 0.42 days in the placebo group (P value ≤ 0.001). Furthermore, significant differences in the pain intensity between Iralvex and placebo group measured on days 1, 3, and 5 were obtained (P value ≤ 0.01). Conclusion. The results of this study show that Iralvex gel is effective and cheap remedy for treatment of RAS without side effects. This trial is registered with IRCT201207253251N3 .